Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
a
x
2
+
b
x
+
c
=
0
the two roots of the equation take the form
x
1
,
2
=
−
b
±
√
b
2
−
4
a
c
2
a
So, start by adding
−
5
to both sides of the equation to get
2
x
2
+
x
−
5
=
5
−
5
2
x
2
+
x
−
5
=
0
Notice that you have
a
=
2
,
b
=
1
, and
c
=
−
5
. This means that the two solutions will be
x
1
,
2
=
−
1
±
√
1
2
−
4
⋅
2
⋅
(
−
5
)
2
⋅
2
x
1
,
2
=
−
1
±
√
41
4
You can simplify this if you want to get
x
1
=
−
1
+
√
41
4
≅
1.35078
and
x
2
=
−
1
−
√
41
4
≅
−
1.85078
Answer:
(2x-2)=
+2 =+2
(2x)=2
----------
2
x= 1
-----------------------------------------------
(x+5)=
-5=-5
x= -5
Step-by-step explanation:
You just need to separate the variable from the numbers
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.